Body composition and physical performance in children after renal transplantation - Feber, Janusz; Dupuis, J. M; Chapuis, F; Braillon, P; Jocteur-Monrozier, D; Daudet, G; So, S; Levrey, H; Hadj-Aissa, A; Martin, X; Bellon, G; Cochat, P (Nephron, 1997)
Body composition using standard anthropometric methods and dual-energy X-ray absorptiometry (DEXA) was determined in a cross-sectional study among 26 pediatric renal transplant recipients. At the same time, spiroergometry exam, pulmonary function tests, dynamometry and tremometry exams were performed in all patients. Fat body mass obtained by DEXA correlated inversely with maximal physical load during spiroergometry exam (r2 = 0.51, p = 0.0001). The study demonstrates good tolerance of increased physical load in children after renal transplantation. An inverse relationship was found between fat body mass and physical performance. Exercise training programs for children after renal transplantation are therefore suggested.
Keywords: Postoperative Period; Male; absorpční fotometrie; Kidney Failure, Chronic; Adolescent; chronické selhání ledvin; Ergometry; Child; ergometrie; dítě; Spirometry; mužské pohlaví; Exercise; spirometrie; mladiství; Hemodynamics; pooperační období; lidé; ženské pohlaví; Kidney Transplantation; transplantace ledvin; Humans; Body Mass Index; složení těla; Body Composition; index tělesné hmotnosti; hemodynamika; Female; cvičení; Absorptiometry, Photon